Perancangan Sistem Penerimaan Siswa Baru Berbasis Web Menggunakan Framework Codeigniter (Studi Kasus : SMP Negeri 5 Jagoi Babang) - Sofia Sofia; Magdalena A. Ineke Pakereng (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Design of the New Student Registration System at SMPN 5 Jagoi Babang is still manual, which requires filling out the registration form with the one submitted by the registration committee, so that prospective new students have to come directly to school and it takes a long time. The web is used in developing a system where new students must be able to input data via the web. The Codeigniter Framework method is used because the system can adjust to changes in the acceptance of new students. The results obtained in the design of the Web Based New Student Admissions System Using the Codeigniter Framework are the convenience for new students to register at SMPN 5 Jagoi Babang, so that it can make it easier for the committee to manage the data of new students who register and Information on the announcement of new student admissions. Keywords— Registration, Admissions, Students, Codeigniter Framework.